Socialization and Physiotherapy Services to Youth Drugs Rehabilitation in Tanon Village, Sragen - Noor Iman, Fidiantari; Wahyuni, W (Riviera Publishing, 2022)
Tanon is a sub-district in Sragen Regency, Central Java Province, Indonesia. Drug rehabilitation is one of the efforts to save addicts from the shackles of drugs and the dangers that accompany them; there are three stages of drug rehabilitation in Indonesia, namely medical, non-medical, and advanced rehabilitation. The implementation of the examination activities for adolescents was carried out using a descriptive method, namely providing an explanation of the benefits of physical examination exercises and introducing the role of physiotherapy to adolescents. In this study, the authors included age and health status characteristics in adolescent rehabilitation at the Indonesian Lentera Bangsa Foundation. Drug rehabilitation is one of the efforts to save addicts from the shackles of drugs and the dangers that accompany them; there are three stages of drug rehabilitation in Indonesia, namely medical, non-medical, and advanced rehabilitation. Specific data presenting a physical examination includes an examination of body conditions such as tests of balance, endurance, and agility of adolescents aged 16-25 years before a physical examination and after being given a physical examination, as well as the level of knowledge of adolescents about the function and role of physiotherapy. The results of data from respondents or adolescents indicate that the average level of knowledge about the role of physiotherapy and the benefits of providing physical exercise is in the